2021
DOI: 10.1002/col.22731
|View full text |Cite
|
Sign up to set email alerts
|

Color preference and contributing factors of urban architecture based on the selection of color samples—Case study: Shanghai

Abstract: The research on citizens' color preference is an important prerequisite for the scientific formulation of urban color planning. Color preferences are normally identified over the Internet or through questionnaire surveys and adjective descriptions. But the analysis has its limitations due to the uncertainty of color descriptions. Based on the quantitative analysis of the three attributes of hue, blackness, and chromaticness, this article obtains the inherent law of color preference of citizens, and compares it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The dominant color in these vigne es is white, which symbolizes purity, simplicity, and elegance. In addition to white, these vigne es also incorporate accents of higher-purity reds, yellows, and blues, creating pops of color that draw a ention and create focal points within the park [24].…”
Section: Exploration Of Park Landscape Color Design Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant color in these vigne es is white, which symbolizes purity, simplicity, and elegance. In addition to white, these vigne es also incorporate accents of higher-purity reds, yellows, and blues, creating pops of color that draw a ention and create focal points within the park [24].…”
Section: Exploration Of Park Landscape Color Design Methodsmentioning
confidence: 99%
“…The dominant color in these vignettes is white, which symbolizes purity, simplicity, and elegance. In addition to white, these vignettes also incorporate accents of higher-purity reds, yellows, and blues, creating pops of color that draw attention and create focal points within the park [24]. In this section, the selection of Zhuhai Shijingshan Park typifies the quintessential characteristics of a marine city environment, rendering it an ideal setting to evaluate how well IGAs could generate contextually relevant and aesthetically pleasing color palettes.…”
Section: Exploration Of Park Landscape Color Design Methodsmentioning
confidence: 99%
“…Internal factors like RGB and HSV also impact color preference. For example, Gou et al [8] studied residents' preferences for the color of urban buildings and found that several factors influence citizens' hue preferences, including gender, age, occupation, monthly income, and cultural background, such as men engaged in business management or professional occupations tending to prefer red-blue, blue, blue-green, green, and neutral colors. On the other hand, women who are teachers or white-collar workers tend to prefer warmer and more vibrant colors like yellow, red, and red-yellow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, colour preferences may vary across regions. For example, people in Antalya, Türkiye, tend to favour cool hues, such as blue, purple and green, for building facades [5], whilst people in Shanghai, China, tend to prefer warm and light hues (e.g., red) and moderate-to-low chroma [6]. Exploring the similarities in the preferences of regional groups has significant and positive impacts on the urban development process [7].…”
Section: Introductionmentioning
confidence: 99%